If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3m = 4m + 5 Reorder the terms: 3m = 5 + 4m Solving 3m = 5 + 4m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-4m' to each side of the equation. 3m + -4m = 5 + 4m + -4m Combine like terms: 3m + -4m = -1m -1m = 5 + 4m + -4m Combine like terms: 4m + -4m = 0 -1m = 5 + 0 -1m = 5 Divide each side by '-1'. m = -5 Simplifying m = -5
| b+19.8=9.2 | | j--14=-20 | | 8n^2-7=121 | | a/4-a-1/8=9/8 | | 6r^2+5=11 | | 3x+6(x-9)=3(x-12) | | 56=4m | | q/6=23 | | r^2-1=80 | | n+13=87 | | s-2=67 | | 10=5-d | | h=-0.13(d-5)2+13 | | 7x-9x-2=4x+6 | | 7x-8=5x-10 | | 94=g+2 | | 4k=36 | | 3e^2x=27 | | -62=f+-20 | | 2x*2+8x+28=0 | | 3G=6 | | 13m-22=9m+6 | | 2f=2 | | A=5/42 | | 11/8b=33 | | 4x-40+x+20+x=180 | | -9/v-6 | | ((5x^2)/(6-3x))/((2x-1)/(4-x^2)) | | 8x+2x-10=0 | | 7+2x=6x-6 | | (-3/2)3 | | 0=(3.88+(x-3.88)) |